A Glow before Darkness: Toxicity of Glitter Particles to Marine Invertebrates - Abessa, Denis Moledo de Souza [UNESP]; Albanit, Letícia França [UNESP]; Moura, Pedro Henrique Paixão de [UNESP]; Nogueira, Vitória Soares [UNESP]; Santana, Felipe Teixeira [UNESP]; Fagundes, Kainã [UNESP]; Ueda, Maysa [UNESP]; Muller, Otto Patrão de Oliveira; Cesar-Ribeiro, Caio [UNESP] (MDPI, 2023)
Glitter particles are considered a model of microplastics, which are used in a wide range of products. In this study, we evaluated the toxicity of two types of glitter (green and white, with distinct chemical compositions) dispersions on the embryonic development of the sea urchins Echinometra lucunte, Arbacia lixula, and the mussel Perna perna. The Toxicity Identification and Evaluation (TIE) approach was used to identify possible chemicals related to toxicity. Glitter dispersions were prepared using 0.05% ethanol. The tested dispersions ranged from 50 to 500 mg/L. The white glitter was composed of a vinyl chloride–methyl acrylate copolymer. The effective concentrations of green glitter to 50% embryos (EC50) were 246.1 (235.8–256.4) mg/L to A. lixula, 23.0 (20.2–25.8) mg/L to P. perna and 105.9 (61.2–150.2) mg/L, whereas the EC50 of white glitter to E. lucunter was 272.2 (261.5–282.9) mg/L. The EC50 for P. perna could not be calculated; however, the lowest effect concentration was 10 mg/L—that was the lowest concentration tested. The filtered suspension of green glitter had Ag levels exceeding the legal standards for marine waters. TIE showed that metals, volatiles, and oxidant compounds contribute to toxicity. The results showed that glitter may adversely affect marine organisms; however, further studies are necessary to determine its environmental risks.
Keywords: chronic toxicity; contaminants of emerging concern; ecotoxicology; marine pollution; microplastics